2014
DOI: 10.3892/mmr.2014.2214
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 inhibits migration of trophoblast cells and contributes to the pathogenesis of severe preeclampsia by regulating endothelial nitric oxide synthase

Abstract: The aim of the present study was to characterize the role of microRNA (miR)-155 in the pathogenesis of severe preeclampsia (PE). A total of 19 severe preeclampsic and 22 normal placentas were collected to measure miR-155 and endothelial nitric oxide synthase (eNOS) expression using quantitative (q)PCR and western blot analysis. The results demonstrated a significant increase in the levels of miR-155 and decreased eNOS expression in the severe preeclampsic placentas, as compared with the normal controls. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 28 publications
(24 reference statements)
2
44
1
1
Order By: Relevance
“…Some miRNAs are reported to be deregulated in the placenta of preeclampsia, further studies revealed that they were related to angiogenesis, inflammation and trophoblast cell migration/invasion [20,[22][23][24][25][26][27][28][29]. Thus far, it remains to be clarified that how the deregulated miRNAs involve in the development of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some miRNAs are reported to be deregulated in the placenta of preeclampsia, further studies revealed that they were related to angiogenesis, inflammation and trophoblast cell migration/invasion [20,[22][23][24][25][26][27][28][29]. Thus far, it remains to be clarified that how the deregulated miRNAs involve in the development of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Several previously studies found about 600 miRNAs expressed in human placenta and profiled genomewide expression of miRNAs in normal and preeclamptic placentas [13][14][15][16][17][18][19]. Although little is known about what roles of miRNAs play in human placenta development and functions, recent reports suggested that preeclampsia-associated aberrant expressed miRNAs play critical roles in human placentas development and function via regulating specific genes with various cell functions [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of miR-378a-5p and miR-376c enhanced these processes [77, 78]. So far, only a handful of miRNAs, including miR-424 [79], miR-101 [52], miR-18a [46], miR-335 [50], miR-137 [55], and miR-155 [61], have been implicated in trophoblast dysfunction through various targets, including endothelial nitric oxide synthase (eNOS) and soluble vascular endothelial growth factor receptor 1 (sVEGFR-1 or sFlt-1).…”
Section: Placental Micrornamentioning
confidence: 99%
“…In addition, miR-155 was linked to the trophoblast function, including proliferation, invasion, and differentiation [59, 60]. Recently, miR-155 was shown to modulate eNOS expression in trophoblast cells [61]. Another highly studied miRNA, miR-210, was first identified in trophoblast cells as an iron metabolism regulator responding to hypoxia stress and implicated in the defective placentation [71].…”
Section: Placental Micrornamentioning
confidence: 99%
“…Another miRNA that is consistently overexpressed in preeclampsia is miR-155 [32,42,69,72] and studies have indicated that miR-155 is important to the regulation of trophoblast invasion [72,86]. miR-155, a common target of a large range of inflammatory mediators, is able to be upregulated by a range of inflammatory factors including interferon b, lipopolysaccharide, TNF-a, and IL-1b; this occurs via the TLR [87].…”
Section: The Roles Of Mirnas In Trophoblast Proliferation Survival Amentioning
confidence: 99%